Integration of Artificial Intelligence (ChatGPT) into Science Teaching and Learning - Hisbulloh Als Mustofa; Aina Jacob Kola; Isaac Owusu-Darko (International Journal of Ethnoscience and Technology in Education, 2025)
The integration of artificial intelligence (AI) into science education is transforming teaching and learning by offering innovative solutions to complex challenges. This study aims to review current trends in AI utilization, particularly ChatGPT, and explore its potential to improve problem-solving in science education. A systematic literature review was conducted using PRISMA guidelines, complemented by experiential exploration and qualitative insights from a thermodynamics lecturer. The findings highlight AI’s ability to provide accurate explanations, generate diverse educational materials, and support interactive learning. However, limitations were identified, including inaccuracies in handling advanced or ambiguous problems and the potential for overreliance by students. Technical and ethical challenges, such as infrastructure requirements, educator preparedness, and concerns about bias, were also noted. These limitations underscore the importance of human oversight and critical evaluation of AI-generated content. The study recommends enhancing AI’s contextual understanding, visualization capabilities, and adaptability to individual learner needs. By harmonizing AI-driven innovations with traditional teaching methods, educators can leverage these tools to create inclusive and effective learning environments, advancing the transformative potential of AI in science education.